¿Una ciudad dividida y polarizada, o una megalópolis policéntrica y plural? El caso crucial y enigmático de la capital para el estudio de la polarización socioterritorial del voto en México - Sonnleitner, Willibald (El Colegio de México A.C., 2024)
This article studies the socio-territorial polarization of the vote in Mexico City, in comparative and historical perspective. Political polarization affects a growing number of democracies. However, despite the intuitive nature of the concept, there is no consensus on its definition, nor on its origins and consequences. The debate is marked by the case of the United States, characterized by a bipartisan and centrifugal polarization towards two opposing extremes that are becoming both increasingly distant from each other as well as more cohesive. In Mexico, by contrast, polarization occurs in a context of party erosion, volatility and fragmentation, with a centripetal dynamic that sets a pragmatic and hybrid government coalition against an even more heterogeneous opposition front in ideological, geographic, and socio-cultural terms. The study of this key case provides tools to understand and measure the socio-territorial polarization of the vote in the capital, and to place it in the Mexican and international context.